DEVELOPING MULTIMEDIA TECHNOLOGY FOR EFL CLASSROOMS IN INDONESIA USING ADDIE MODEL: A LITERATURE REVIEW - Annisa Hafizah Gamal (ELTR Journal, 2023)
Most academic learning situations involve multimedia learning since students encounter words and graphics, ranging from multimedia encyclopedias to online educational games to textbooks. Multimedia has become increasingly used to help learning and cognition. As technology advances, educators are required to be more creative when creating learning devices. Teachers and lecturers need to develop an instructional design that can address the needs of the students. ADDIE model is one of the most effective tools in developing educational products and other learning resources, including multimedia technology. This paper attempts to explore how multimedia in various levels of EFL classrooms in Indonesia are developed using the ADDIE model in particular. Nationally accredited articles were categorized based on similar themes to multimedia development using ADDIE model to be analyzed. Most of the articles showed a successful development and implementation of the media used in teaching reading, listening, writing vocabulary, and language functions. The multimedia: worksheets, websites, applications, cards, and videos, are mostly rated highly by the expert. The validity and practicality were also high. However, some of the articles did not mention the principles and details of the process of multimedia development.